Soil quality assessment of Uruguayan agricultural soils - Morón, Alejandro; Quincke, Andrés; Molfino, Juan; Ibáñez, Wilfredo; García, Adriana (Agrociencia Uruguay, 2012)
The process of agricultural intensifi cation in Uruguay brought up questions about the impacts on the soil. In order to analyze the soil quality status in the departamentos of Soriano and Río Negro, we sampled 108 fi elds to determine soil organic carbon (SOC) and potentially mineralizable nitrogen (PMN). Average losses were 20% in SOC and 42% in PMN in the 0-15cm sampling depth. About one third of the sampled fi elds had losses between 30 and 60% in SOC and between 35 and 80% in PMN. Losses in SOC and PMN varied among edaphic environments. Results about the effects of soil use and management on SOC and PMN are not conclusive. This paper concludes with reference values for SOC and PMN for the different edaphic environments studied.